Associations between intergenerational transmission of AD, type 2 diabetes, and cognitive function among non‐Hispanic Black adults in midlife. (20th December 2022) - Kraal, A.Zarina; Palta, Priya; Brickman, Adam M.; Manly, Jennifer J
Abstract: Background: Type 2 diabetes (T2D) and parental history of Alzheimer's disease (AD) are independent risk factors for late‐life cognitive impairment. The presence of T2D may strengthen the association of parental AD risk on cognition through pathways of vascular function, insulin signaling, and amyloid β/tau metabolism. Examining the independent and interactive association of parental AD risk and T2D on cognitive function, specifically in non‐Hispanic Black adults may advance our understanding of their contribution to the disproportionate rates of AD in this group. We hypothesize that parental AD risk and T2D would be independently associated with worse cognition and that the association between parental AD risk and cognition would be stronger in participants with T2D. Method: Participants comprised non‐Hispanic Black adults (N = 331; 25.8% with T2D; Table 1) in the Offspring Study who are the adult children of participants in the Washington Heights Inwood Columbia Aging Project (WHICAP). AD risk was operationalized as parental memory performance residualized for age and education and assessed at their last WHICAP visit. Participant T2D was based on self‐reported physician diagnosis and cognition was assessed with measures of attention, language, and memory. Cognitive test scores were residualized for age and education (Table 1). Linear regression models quantified the independent associations and interaction of AD risk and T2D on offspring cognition. Result: T2D was associated with lower language ( B = ‐0.13, 95% CI: [‐0.55, ‐0.08]) and memory ( B = ‐0.45, 95% CI: [‐0.72, ‐0.17]) scores, but AD risk was not associated with cognition in any domain. However, AD risk was associated with lower language scores among participants without T2D, but not in participants with T2D ( B = ‐0.36, 95% CI [‐0.71, ‐0.02]; Figure 1). No interaction was observed for AD risk and T2D with memory and attention (Figure 2). Conclusion: Our results suggest that among middle‐aged non‐Hispanic Black adults, AD risk is associated with lower language performance in individuals without T2D. The association between AD risk and cognition may be masked by exposure to risk factors, such as T2D.